Quantum dot based immunosensor using 3D circular microchannels fabricated in PDMS - Morarka, Amit; Agrawal, Shailaja; Kale, Sonia; Kale, Anup; Ogale, Satishchandra B.; Paknikar, Kishore; Bodas, Dhananjay S. (Biosensors & Bioelectronics, 2011)
Microchannel is basic functional component of microfluidic chip and every step-forward of its construction technique has been receiving concern all over the world. The present work describes a novel, rapid and simple fabrication technique for building 3D microchannels in poly(dimethyl siloxane) (PDMS) elastomer. These microchannels were used for rapid detection of antigens (E. coli) by quantum dot (QD) based approach. Luminescent QD (CdTe) were synthesized by aqueous method and characterized using high resolution transmission electron microscopy (HRTEM), fluorescence spectroscopy and X-ray diffraction (XRD). The QDs were functionalized with anti-E. coli antibodies for immuno-detection. The reported process allowed easier and faster method of fabrication of circular 3D micochannels and demonstrated their potential use in an immuno-biosensor device. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Capillary driven flows; Circular microfluidics; Immunosensor; QDs

Reduced graphene oxide modified electrodes for sensitive sensing of gliadin in food samples - Chekin, Fereshteh; Singh, Santosh K.; Vasilescu, Alina; Dhavale, Vishal M.; Kurungot, Sreekumar; Boukherroub, Rabah; Szunerits, Sabine (ACS Sensors, 2016)
Incidences of food allergies are on the rise, which can greatly affect the well-being of children as well as adults. Intolerance to gluten, a protein composite of gliadin and glutenin, present in wheat, barley, and rye and several cereals, can be the causative agent of celiac disease (CD) and other allergic reactions. A gluten-free diet has become essential for people affected by CD, and consequently, the amount of gluten in food products needs to be strictly controlled. In this paper, we report an electrochemical label-free immunosensor for ultrasensitive and specific detection of gliadin. The sensor takes advantage of the specific properties of porous reduced graphene oxide (prGO) covalently functionalized with anti-gliadin antibodies using 1-pyrenecarboxylic acid as linker molecule. Using differential pulse voltammetry (DPV) and [Fe(CN)6](3-/4-) as a redox probe, a decrease of current is linked to the presence of gliadin. The sensor achieved a detection limit of 1.2 ng mL(-1) over a 1.2-34 ng mL(-1) linear range with high selectivity. The advantages offered by this sensor are the possibility to regenerate the surface of the immunosensor, its rapid and ease of production, as well as applicability for the screening of gliadin concentrations in real food samples, as shown here.
Keywords: anti-gliadin antibody; food samples; gliadin; Immunosensor; Porous reduced graphene oxide